ALLELE FREQUENCIES IN MULTIGENE FAMILIES - S. Padmadisastra (Journal of the Indonesian Mathematical Society, 2010)
Results on allelle frequencies in three chromosomes, drawn at randomfrom a diploid population, evolving in equilibrium, at a particular generation, arepresented in this paper. The genes on each chromosome are subject to unbiased andreciprocal gene conversion and mutation. Using the coalescent approach we find theprobability distribution of the allelic configurations in the three chromosomes, andthe moments of the allelic numbers that exist in one of the three chromosomes orin a pair of chromosomes. We also consider the identity coefficients of two genesdrawn at random, one from each of two chromosomes, and the probability that allgenes in the three chromosomes are monomorphic. Numerical examples are alsogiven together with simulation results, and they agree well.DOI : http://dx.doi.org/10.22342/jims.16.2.33.89-104